Strategic Financial Decision-Making in Manufacturing: Assessing Investment, Earnings Disposition, and Growth Dynamics - Andi Mulyadi Radjab (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study explores the impact of investment decisions, profit disposition, equity growth, and operating decisions on growth potential and firm value in the manufacturing sector on the IDX. It is quantitative research with inferential statistics and secondary data analysis according to the conceptual framework using structural equation modeling. The results show that investment decisions and profit disposition have a significant, albeit negative, impact on firm growth potential, but have no significant effect on firm value. On the other hand, internal capital growth and operational decisions have no significant effect on firm value. These findings emphasize the importance of knowledge-based decision-making in managing financial and operational aspects to support sustainable growth and enhance firm value. Firms need to consider the impact of investment decisions and profit disposition on potential growth, as well as other factors that affect firm value in a dynamic market.